STRATEGI KAMPANYE PARTAI ISLAM: KASUS PARTAI KEADILAN SEJAHTERA PADA PEMILU 2019 - Trianggorowati, Erna; Al-Hamdi, Ridho; Erna Trianggorowati; Ridho Al-Hamdi (Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract: This article examines the campaign strategy of the Islamist party, namely PKS in the 2019 legislative election. It is fascinating to be investigated further because this party can ward a lot of predictions and surveys which stated that PKS could not exceed the parliamentary threshold of four percent. PKS has an outstanding performance and can reach 8.62 percent. Methodologically, this study is a qualitative research by applying the case study approach. For data-gathering, this study collects data and information through social media such as news channels and social networking sites. In the analysis process, this uses the mix marketing theory consisting of four Ps (4P), i.e., product, price, place, and promotion. On the product, PKS promotes four main programs: reinforcing the realization of the driving license for the long-life term, removing the motorcycle tax, protecting Muslim scholars, and removing the wage tax for eight billion IDR per month. Concerning the price, PKS spent roughly 150 Billion IDR. On the place or distribution, the PKS’ legislative candidates did socialize to the grass-root with various activities. Meanwhile, regarding the promotion, PKS promotes itself through event publications and social media conducted by its cadres and devotees. The most significant strategy which affects to the increase of PKS’ vote in 2019 is the promotion mainly the event publication with roadside flashmob activities. Indeed, the cadres and devotees’ loyalty has a significant role as the vote-getters in mobilizing electorate. Keywords: Campaign Strategy,PKS, Legislative Election, Flashmob Abstrak: Artikel ini mengkaji tentang strategi kampanye partai Islam yaitu PKS pada pemilihan legislatif tahun 2019. Penelitian ini menarik dilakukan karena keberhasilan PKS dalam menepis asumsi berbagai lembaga survei yang memprediksi PKS tidak lolos ambang batas parlemen. PKS berhasil meningkatan suaranya hingga di 8,62 persen. Secara metodologis, artikel ini merupakan hasil penelitian kualitatif dengan penggalian sumber data dari berbagai berita terpercaya di media massa online. Sebagai kerangka analisa, penelitian ini menggunakan teori mix marketing (4P) yang terdiri dari empat indikator: produk, harga, penempatan/distribusi, dan promosi. Pada indikator produk, PKS menjual empat program unggulan: pemberlakuan SIM seumur hidup, pembebasan pajak bermotor, perlindungan ulama, tokoh agama dan simbol agama, pembebasan pajak penghasilan di bawah Rp. 8 juta. Pada indikator harga, PKS mengeluarkan biaya kurang lebih Rp. 150 Milyar. Pada indikator penempatan, para caleg melakukan sosialisasi melalui beragam kegiatan. Sementara itu, pada indikator promosi, PKS melakukan kegiatan flashmob dan disebarluaskan melalui media sosial. Dari empat indikator tersebut, PKS lebih menekankan pada strategi promosi melalui publikasi even terutama kegiatan flashmob di pinggir jalan berkat loyalitas kader dan simpatisan PKS sebagai motor penggerak sekaligus pengepul suara partai di Pemilu 2019.Kata Kunci: Strategi Kampanye, PKS, Pileg, Flashmob